Development of games-based learning media "Eco Quest: guardian of the element" on the subject of climate change and global warming for class X high school - Riski Amelia; Devi Yulianty Surya Atmaja; Dadi Rusdiana (Universitas Ahmad Dahlan, 2024)
This study aims to develop "Eco Quest: Guardian of the Elements" as an educational tool to enhance students' understanding of climate change and global warming concepts. The learning medium utilizes a game-based learning approach to make learning physics concepts engaging and interactive. This media aims to help students grasp complex concepts and foster a greater interest in physics. The research follows a research and development (R&D) methodology, explicitly employing the ADDIE model. The study involved 35 tenth-grade high school students as participants. During the development stage, validation data was gathered from media experts, including lecturers, to assess the effectiveness of the developed media. Pretest and posttest results revealed a 23-point improvement in student comprehension, with an N-Gain score of 37%. Overall, the "Eco Quest: Guardian of the Elements" learning tool has proven effective in enhancing students' understanding of climate change and global warming concepts. However, further research is recommended to investigate the long-term effects of this medium on students' attitudes, knowledge, and behavior regarding these issues.